Effects of nickel and nitrogen soil fertilization on lettuce growth and urease activity - Oliveira, Thomas Carlos; Fontes, Renildes Lúcio Ferreira; Rezende, Sebastião Tavares de; Alvarez V., Víctor Hugo (Revista Brasileira de Ciência do Solo, 2013)
Nickel is a micronutrient involved in nitrogen metabolism and a constituent of the urease molecule. Plant growth and urease activity were evaluated in lettuce (Lactuca sativa L.) grown in soil-filled pots in a 2 x 8 factorial design with two nitrogen (N) sources and eight Ni rates, with five replications. Nitrogen was applied at 200 mg dm^-3 (half the dose incorporated into the soil at seedling transplanting and half top-dressed later) using the sources NH4NO3 (AN) and CO(NH2)2 (Ur). The Ni treatments (0, 2, 4, 8, 12, 16, 24 and 32 mg dm^-3) were applied as NiCl2. The shoot dry-matter yield, leaf urease activity, Ni levels in the lettuce leaves and Ni levels extracted from soil with Mehlich-3 (M-3) and DTPA were determined. In the plants supplied with AN, the shoot dry-matter yield was higher than in those supplied with Ur. There was no difference in shoot dry matter in response to soil-applied Ni. The leaf urease activity increased with Ni application, regardless of the N source. The extractions with M-3 and DTPA were efficient to evaluate Ni availability for lettuce in the Red-Yellow Latosol.

Níquel é um micronutriente envolvido no metabolismo de nitrogênio e é componente da molécula da urease. Foram avaliados o crescimento de plantas e a atividade da urease em alface (Lactuca sativa L.) cultivada em solo em vasos, em experimento fatorial 2 x 8, com duas fontes de nitrogênio (N) e oito doses de Ni, com cinco repetições. O N foi aplicado ao solo (200 mg dm^-3), incorporando-se metade no transplantio das mudas e a outra metade, mais tarde, na superfície do solo, utilizando-se nitrato de amônio (NH4NO3) e ureia [CO(NH2)2]. Os tratamentos com Ni (0, 2, 4, 8, 12, 16, 24 e 32 mg dm^-3) foram aplicados, usando-se cloreto de níquel (NiCl2). Produção de matéria seca, atividade da urease e do Ni nas folhas de alface e Ni no solo (Mehlich-3 e DTPA) foram determinados. A produção de matéria seca nas plantas supridas com NH4NO3 foi maior do que nas supridas com CO(NH2)2. Não houve diferença na produção de matéria seca das folhas em resposta à aplicação de Ni ao solo. A atividade da urease aumentou com o incremento das doses de Ni, mas não se alterou em razão da fonte de N utilizada. As extrações com Mehlich-3 e DTPA foram eficientes para avaliar a disponibilidade de Ni para alface no Latossolo Vermelho-Amarelo.
Keywords: Ammonium nitrate; Urea; Plant nutrition; Lactuca sativa L.